IMPLIKASI PERUBAHAN TARIF DANA REBOISASI DAN PROVISI SUMBER DAYA HUTAN TERHADAP LABA PEMEGANG KONSESI HUTAN DAN PENERIMAAN NEGARA BUKAN PAJAK: STUDI KASUS HUTAN ALAM PRODUKSI DI KALIMANTAN TIMUR, INDONESIA - Satria Astana; Soenarno Soenarno; OK Karyono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
The decline of natural forest timber production has suppressed non-tax revenues (PNBP) of forestry sector. To anticipate further decrease in PNBP the government has been trying to raise tariffs of PSDH and DR. This research aims to study the implications of DR and PSDH tariff increases on profits of forest concessionaires and PNBP of forestry sector, and the potential use of logging waste as an additional source of PNBP. The data collected include: 1) the cost of forest management; 2) the price of logs and 3) logging waste. Data of forest management cost and log price were obtained from the documents and interviews with forest managers, while logging waste data was obtained by measuring in the field. The results of the study reveal that the increases in DR and PSDH tariffs simultaneously would cause the profit of company decreased by 22.3%, while the PNBP increased by 29.7%. The study suggest: 1) the policy on increasing DR tariff may be directly applied, while the pricing of logs at the landing site should be based on a rational determination method and 2) increases in DR and PSDH tariffs need to consider the amount of logging waste in the forest.